Inactivated Vaccines Against SARS-CoV-2: Neutralizing Antibody Titers in Vaccine Recipients - Zhang, Haiying; Jia, Yuyuan; Ji, Ying; Cong, Xu; Liu, Yan; Yang, Ruifeng; Kong, Xiangsha; Shi, Yijun; Zhu, Ling; Wang, Zhenyu; Wang, Wei; Fei, Ran; et al. (Frontiers in Microbiology, 2022)
Background: Although effective vaccines have been developed against coronavirus disease 2019 COVID-19, the level of neutralizing antibodies (NAbs) induced after vaccination in the real world is still unknown. The aim of this work was to evaluate the level and persistence of NAbs induced by two inactivated COVID-19 vaccines in China. Methods: Serum samples were collected from 1,335 people aged 18 years and over who were vaccinated with an inactivated COVID-19 vaccine at Peking University People's Hospital from January 19 to June 23, 2021, for detection of anti-severe acute respiratory syndrome coronavirus 2(SARS-CoV-2)antibodies. Results: The positive rate for NAbs against SARS-CoV-2 was 79% ~ 91% from the first month to the second month after the second vaccine dose. The gradual decline in positivity rate for NAb response was observed from 78% at 3 months post vaccination to 0% at 12 months post vaccination. When there was a 21-day interval between two doses of vaccine, the NAb positive rate was 0% 6 months after the second dose. NAbs levels were significantly higher when the interval between two doses were 3-8 weeks than when it was 0-3 weeks. There was a linear correlation between NAbs and IgG antibodies in 1335 vaccinated patients. NAb levels decreased in 31 patients (81.6%) and increased in 7 patients (18.4%) over time in the series of 38 patients after the second vaccination. The NAb-positive rate of NAbs was significantly higher in 18- to 40-year-old subjects than in 41- to 60-year-old subjects . Conclusions: The NAb-positive rate of was the highest at the first and second month after the second dose of vaccine dose, and gradually decreased over time. With a 21-day interval between two doses of vaccine, neutralizing antibody levels persisted for only six months after the second dose of vaccine. Therefore, a third vaccine dose is recommended. Our results suggest that in cases in which NAbs cannot be detected, IgM/IgG antibodies can be detected instead. The level of NAbs produced after vaccination was affected by age but not by sex. Our results suggest that an interval of 21 to 56 days between shots is suitable for vaccination.